Effective Deep Features for Image Splicing Detection - Ahmed I.T.; Hammad B.T.; Jamil N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Correlation methods; Deep learning; Image classification; Image enhancement; Alexnet model; Canonical correlation analyse classifier; Canonical correlations analysis; Deep feature; Digital image; Digital image forgery; Image forgery; Image forgery detections; Image splicing; Image splicing detection; Classification (of information)